Repeat and Relapsing Peritonitis Microbiological Trends and Outcomes: A 21-Year Single-Center Experience. (30th January 2021) - Reis, Marina; Ribeiro, Catarina; Gomes, Ana Marta; Santos, Clara; Lopes, Daniela; Fernandes, João Carlos
Abstract : Peritonitis is a major peritoneal dialysis complication. Despite a high cure rate, relapsing and repeat peritonitis is associated with Tenckhoff catheter biofilm and multiple episodes of peritoneal damage. In relapsing peritonitis, prompt catheter removal is mandatory; otherwise, in repeat peritonitis, there is not a clear indication for catheter removal. It is questionable if the approach to removal should be different. There are few recent data on repeat and relapsing peritonitis microbiology and clinical outcomes since most studies are from the past decade. This study evaluates the microbiology, clinical outcomes, and impact of relapsing and repeat peritonitis on technique survival and the impact of catheter removal in development of further peritonitis episodes by the same microorganism. We developed a single-center retrospective study from 1998 to 2019 that compared repeat and relapsing peritonitis with a control group in terms of causative microorganisms, cure rate, catheter removal, and permanent and temporary transfer to hemodialysis. We also compared repeat and relapsing peritonitis clinical outcomes when Tenckhoff catheter was not removed. Comparing to the control group, the repeat/relapsing group had a higher cure rate (80.4% versus 74.5%, p = 0.01 ) and lower rate of hospitalization (10.9% versus 27.7%, p = 0.01 ). Technique survival was superior in the repeat/relapsing group (log rank = 4.5, p = 0.03 ). Gram-positive peritonitis was more common in the repeat/relapsing group especially Streptococci viridans (43.5% versus 21.3%, p = 0.01 ) and Gram-negatives in the control group (26.6% vs 9.0%, p = 0.02 ). When the Tenckhoff catheter was not removed after a repeat episode, 58.6% developed a new repeat/relapsing episode versus 60.0% in the relapsing group. Although repeat and relapsing peritonitis have a higher cure rate, it leads to further episodes of peritonitis and consequent morbidity. When Tenckhoff catheter was not removed, the probability of another peritonitis episode by the same microorganism is similar in repeat and relapsing peritonitis.